2023
DOI: 10.1029/2022gh000749
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Urbanization on the Spatial Distribution of Associations Between Air Pollution and Mortality in Beijing, China

Abstract: Between 1978 and 2020, China experienced a rapid increase in the urban population, from 170 to 902 million, corresponding to an urbanization rate change from 17.9% to 63.9% (National Bureau of Statistics of China, 2022). By 2030, the urbanization rate and total urban population in China are projected to reach 71% and 1,070 million, respectively (Q. Chen et al., 2017). This trend can lead to several consequences for the health of China's population. There is no consensus on whether urbanization is more benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…Prior research has highlighted how socioeconomic factors modify the relationship between environmental exposures and health outcomes. For instance, studies have shown that urban populations have a lower risk of mortality compared to rural areas for the same unit change of PM 2.5 , ozone, and temperature [14,15,20]. Our study further demonstrates that socioeconomic factors not only exacerbate environmental health inequalities by modifying the exposure-response relationship but also amplify these inequalities by influencing prompt responses and protective behaviors.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Prior research has highlighted how socioeconomic factors modify the relationship between environmental exposures and health outcomes. For instance, studies have shown that urban populations have a lower risk of mortality compared to rural areas for the same unit change of PM 2.5 , ozone, and temperature [14,15,20]. Our study further demonstrates that socioeconomic factors not only exacerbate environmental health inequalities by modifying the exposure-response relationship but also amplify these inequalities by influencing prompt responses and protective behaviors.…”
Section: Discussionsupporting
confidence: 63%
“…We further estimated the provincial concentration-response functions by Bayesian hierarchical models, which were widely used in multisite epidemiologic studies to combine risk estimates across sites. We employed provincial-level exposure-response relationships because the exposure-response relationship is influenced not only by physiological vulnerability but also by socioeconomic factors [20]. Provincial-level exposure-response relationships enable consideration of physiological differences among regional populations and mitigate some of the exposure-response disparities attributed to socioeconomic variations.…”
Section: Mortality and Concentration-response Functionsmentioning
confidence: 99%
“…Meanwhile, the overall vulnerability maps (figure 6) can be used for statewide multidisciplinary decision-making. This distinction of different effects of climatic hazards on different urbanization levels has been shown in other places and for other climatic hazards, too, which also suggests potential different patterns in rapidly urbanizing countries [80,81].…”
Section: Discussionsupporting
confidence: 55%